LANGUAGE INTERFERENCE IN TEACHING ENGLISH AS FOREIGN LANGUAGE VIEWED FROM PSYCHOLINGUISTICS - Lina, Marisa Fran (E-Link Journal, 2023)
Learning English as a foreign language for speakers of Indonesian as their mother tongue is sometimes difficult. They are used to speaking and understanding the meaning of Indonesian, then they have to learn a foreign language. This is one of the factors for the occurrence of language interference. In addition, language interference is also very closely related to Psycholinguistics (it studies language and its relationship to human psychology). In this regard, the author also tries to relate the phenomenon of language interference with her experience in teaching English which is considered as a foreign language. The results shows that the author found 8 types of language interference in his English class. From these findings, the writer also tries to find a solution to minimize the students' language interference.